Intrauterine bacterial growth in elective and non-elective caesarean sections - Solt, Ido; Frank Wolf, Maya; Michlin, Rosa; Farajun, Yaniv; Ophir, Ella; Bornstein, Jacob (Journal of obstetrics and gynaecology, 2021)
We assessed intrauterine bacterial growth for elective and non-elective caesarean sections (CSs). Aerobic uterine cultures were obtained from the uterine cavity immediately following placental removal from 1376 patients who underwent CS in one center during one year. About 13.8% (115/832) of elective CS were positive vs. 55.9% (304/544) of non-elective CS ( < .001). Of non-elective CSs, 28.6% (56/196) of those without ruptured membranes (ROM) were positive vs. 71.3% (248/348) with ROM ( < .001). Mean birth weight and 1-minute Apgar scores were significantly lower in women with positive cultures, elective and non-elective, than negative cultures. A higher percentage of women with positive uterine cultures presented with postpartum endometritis ( < .05). Intrauterine bacteria in elective CSs demonstrate that the uterine cavity is not sterile. Non-elective CS, particularly after membrane rupture, is a significant risk factor for positive uterine culture. Positive uterine culture is associated with lower birth weight, lower one-minute Apgar score and postpartum endometritis.Impact statement Postpartum endometritis is a leading cause of postpartum febrile morbidity. Caesarean sections, in particular non-elective cesareans, are an important risk factor for the development of postpartum endometritis. Controversy exists concerning the sterility of the placenta and uterus. The diagnosis of endometritis is based mainly on clinical findings and does not necessitate bacterial isolation from the uterine cavity. Positive culture at caesarean section has been associated with positive postoperative culture and yet, currently, professional organisations do not recommend the routine sampling of intrauterine cultures during caesarean section. Since positive uterine culture rate was higher in non-elective CSs and associated with lower birth weight and 1-minute Apgar score and postoperative endometritis, obtaining uterine culture in those cases might be of clinical value. Obtaining routine intrauterine cultures during non-elective caesarean sections might be useful for detecting significant pathogens and tailoring antibiotic treatment in postpartum endometritis. Further studies are necessary in order to determine the impact of obtaining intrauterine cultures during caesarean sections, particularly non-elective cesareans.